2021
DOI: 10.12968/bjom.2021.29.12.699
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on the delivery of interprofessional education: it's not all bad news

Abstract: During the COVID-19 outbreak, most face-to-face teaching and practice-based learning placements were suspended. Universities provided ongoing health and social care education, including interprofessional education, using online technology. Focusing on changes in the delivery of interprofessional education, this second article in a series on interprofessional education provides an international perspective through facilitators' case reports. It considers the key factors that enabled a rapid shift from face-to-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Additionally, for assessment to be successful it must also be authentic in nature, whether delivered online or face to face (Appiah and Van Tonder, 2018;JISC, 2020;Sutadji et al, 2021) -in other words, ensuring that the knowledge, skills and capabilities gained are applicable in the practice or work setting. Ensuring that the learning outcomes continue to be robustly assessed, while simultaneously creating an authentic learning experience are essential; however, the shift from in-person to online assessment, as reported by Wetzlmair et al (2021) and within the case studies presented here, can prove challenging. As for online delivery, effective replication of face-to-face assessment to a remote learning environment should entail much more than a 'lift and shift approach', and should ideally entail a redesign of the entire learning and teaching process.…”
Section: Discussion and Considerationsmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, for assessment to be successful it must also be authentic in nature, whether delivered online or face to face (Appiah and Van Tonder, 2018;JISC, 2020;Sutadji et al, 2021) -in other words, ensuring that the knowledge, skills and capabilities gained are applicable in the practice or work setting. Ensuring that the learning outcomes continue to be robustly assessed, while simultaneously creating an authentic learning experience are essential; however, the shift from in-person to online assessment, as reported by Wetzlmair et al (2021) and within the case studies presented here, can prove challenging. As for online delivery, effective replication of face-to-face assessment to a remote learning environment should entail much more than a 'lift and shift approach', and should ideally entail a redesign of the entire learning and teaching process.…”
Section: Discussion and Considerationsmentioning
confidence: 95%
“…As interprofessional education activities moved to online delivery, several adaptations had to be implemented to ensure continuity of IPE activity (Wetzlmair et al, 2021). Student engagement in online interprofessional education activities also varied as many students were reluctant to utilise their cameras and some faced technical difficulties.…”
Section: What Adaptations Occurred Due To Covid-19 and What Were The ...mentioning
confidence: 99%
“…Moreover, guidelines for examinations, strict regulations for study courses and a lack of resources make it difficult to implement IPE (Ghebrehiwet et al, 2016;Tong et al, 2016;Busari et al, 2017;Hämel and Vössing, 2017;Findyartini et al, 2019). Frenk et al (2022) discuss new challenges regarding the implementation of IPE in more detail (see also Wetzlmair et al, 2021; for examples of implementation of IPE during the pandemic, see Alrasheed et al, 2021;Engelmann et al, 2021). Many of these are direct consequences of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Online learning opportunities can be developed through partnerships with existing educational institutions, as well as between First Nation governments with common educational goals and values. The move to remote learning throughout the COVID‐19 pandemic has demonstrated that online learning can be an effective delivery method for formal educational programmes (Wetzlmair et al ., 2021). This would allow Indigenous community members in remote and northern locations to remain in their home communities while not foregoing their educational goals.…”
Section: Policy Implications and Conclusionmentioning
confidence: 99%